Laryngeal myxoedema: a literature review of an uncommon complication of hypothyroidism - Iftikhar, Mian Harris; Raziq, Fazal I; Coll, Patrick; Dar, Aneeqa Yousaf (BMJ case reports, 2021)
A 59-year-old woman presented to the emergency department with shortness of breath. She had significant oropharyngeal swelling obstructing her upper respiratory tract. A diagnosis of laryngeal myxoedema was made, which was attributed to severe hypothyroidism. She required invasive ventilation and subsequently a tracheostomy. She was treated with levothyroxine and hydrocortisone. She completely recovered with this therapy. In this review, we will discuss similar cases and different therapeutic options. This case also highlights the fact that establishing a diagnosis of laryngeal myxoedema, a condition that can potentially have lethal outcomes and can be challenging.